Assessing the current distribution of Southwestern Australian shallow-water reef fish assemblages in relation to management bioregions, and the change in these assemblages over time - Goldsworthy, Savita Delphini (Curtin University, 2020)
This research documented the current distribution of shallow-water reef fish along ~2000 km of coastline in Southwest Australia and provided insights into how these assemblages have changed over the last 14 years. Fish communities formed four unique assemblages along the coast, with the boundaries of these assemblages differing from current management regions. These assemblages changed over the 14-year monitoring period with variations in the thermal niche, endemism and trophic level of species present.